2010
DOI: 10.1128/jb.01023-10
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of the Polysaccharide-Degrading, Thermophilic Anaerobe Spirochaeta thermophila DSM 6192

Abstract: Spirochaeta thermophila is a thermophilic, free-living anaerobe that is able to degrade various ␣-and ␤-linked sugar polymers, including cellulose. We report here the complete genome sequence of S. thermophila DSM 6192, which is the first genome sequence of a thermophilic, free-living member of the Spirochaetes phylum. The genome data reveal a high density of genes encoding enzymes from more than 30 glycoside hydrolase families, a noncellulosomal enzyme system for (hemi)cellulose degradation, and indicate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…PCC 8106 (LpcK), Spirochaeta thermophila DSM 6192 (SthK), and Leptospira biflexa serovar Patoc strain (LbiK). Among these species, Trichodesmium, Arthrospira, and Lyngbya belong to the genus of cyanobacteria or blue-green algae, whereas Spirochaeta thermophila is an extremely thermophilic bacterium (24) and Leptospira biflexa is a saprophytic pathogen (25). Alignment of these sequences using ClustalW (26) and further inspection revealed structural motifs that are common among members of the superfamily of voltage-gated K + channels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PCC 8106 (LpcK), Spirochaeta thermophila DSM 6192 (SthK), and Leptospira biflexa serovar Patoc strain (LbiK). Among these species, Trichodesmium, Arthrospira, and Lyngbya belong to the genus of cyanobacteria or blue-green algae, whereas Spirochaeta thermophila is an extremely thermophilic bacterium (24) and Leptospira biflexa is a saprophytic pathogen (25). Alignment of these sequences using ClustalW (26) and further inspection revealed structural motifs that are common among members of the superfamily of voltage-gated K + channels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among isolated strains, S. thermophila , with an optimal growth temperature of 65°C, is the only one that can live on cellulose and hemicellulose substrates . However, genome sequencing revealed that S. thermophila is not equipped with typical cellulosomal proteins such as scaffoldins or cohesins . Instead, its chromosome comprises a broad set of 72 glycoside hydrolases (GH) of which 28 are presumably secretory enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Many new hyperthermophiles from bacteria and archaea have recently been isolated and the genomes of an increasing number have been sequenced [9-17], thus there are plenty of sequences can be obtained from the databases (http://www.ncbi.nlm.nih.gov/, http://www.cazy.org/). The genome sequence of Thermotoga thermarum was also reported last year (GenBank accession number: CP002351).…”
Section: Introductionmentioning
confidence: 99%